2018
DOI: 10.1186/s12984-018-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antagonistic muscle co-contraction on in vivo knee contact forces

Abstract: BackgroundThe onset and progression of osteoarthritis, but also the wear and loosening of the components of an artificial joint, are commonly associated with mechanical overloading of the structures. Knowledge of the mechanical forces acting at the joints, together with an understanding of the key factors that can alter them, are critical to develop effective treatments for restoring joint function. While static anatomy is usually the clinical focus, less is known about the impact of dynamic factors, such as i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 55 publications
3
41
0
Order By: Relevance
“…However, while standard motion analysis measurements and rigid body mechanics can directly determine inter-segmental joint loads and moments, distribution of these loads to muscles, ligaments, and articular contact surfaces remains complicated by the inherent redundancy within the musculoskeletal system, 11 particularily with regards to muscle co-contraction. 44 Thus, in vivo validation remains a major obstacle in widespread acceptance of model predictions of knee loading and hence limits clinical translation of the technology.…”
Section: Introductionmentioning
confidence: 99%
“…However, while standard motion analysis measurements and rigid body mechanics can directly determine inter-segmental joint loads and moments, distribution of these loads to muscles, ligaments, and articular contact surfaces remains complicated by the inherent redundancy within the musculoskeletal system, 11 particularily with regards to muscle co-contraction. 44 Thus, in vivo validation remains a major obstacle in widespread acceptance of model predictions of knee loading and hence limits clinical translation of the technology.…”
Section: Introductionmentioning
confidence: 99%
“…When muscle forces are not included in the calculation of joint load, this may lead to an underestimation of the actual load in the joint (Lloyd and Buchanan, 2001). Several studies already showed a contribution of muscular cocontraction to higher joint CF (Trepczynski et al, 2018;Hoang et al, 2019). Wesseling et al (2018) reported that 12 months after THR surgery the total CF on the ipsilateral knee were still lower compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, the more representative method to quantify muscle co-contraction is through estimating individual muscle forces (Kellis et al, 2003), which may require advanced capabilities in neuromusculoskeletal modeling and simulation. Simulation-based studies can estimate muscle forces and compute CCI with either muscle forces (Trepczynski et al, 2018) or the joint moments generated by individual muscles (Souissi et al, 2018). Since CCI is commonly used by the clinical community, it can be used to investigate the relationship between muscle co-contraction and joint stiffness during gait.…”
Section: Introductionmentioning
confidence: 99%